A ten-year study of midwife-led care at an Austrian tertiary care center: a retrospective analysis with special consideration of perineal trauma - Barbara Bodner-Adler (BMC Pregnancy and Childbirth, 2017)
Abstract Background In contrast to other countries, Austria rarely offers alternative models to medical led-care. In an attempt to improve the facilities, a midwife-led care service was incorporated within the Department of Obstetrics and Fetomaternal Medicine. The aim of the present study was to analyze the maternal and neonatal outcomes of this approach. Methods Over a 10-years period, a total of 2123 low-risk women receiving midwife-led care were studied. Among these women, 148 required obstetric referral. Age- and parity matched low-risk women with spontaneous vaginal birth overseen by an obstetrician-led team were used as controls to ensure comparability of data. Results Midwife-led care management demonstrated a significant decrease in interventions, including oxytocin use (p < 0.001), medical pain relief (p < 0.001), and artificial rupture of membranes (ARM) (p < 0.01) as well as fewer episiotomies (p < 0.001), as compared with obstetrician-led care. Moreover, no negative effects on maternal or neonatal outcomes were observed. The mean length of the second stage of labor, rate of perineal laceration and APGAR scores did not differ significantly between the study groups (p > 0.05). Maternal age (p < 0.01), head diameter (p < 0.001), birth weight (p < 0.001) and the absence of midwife-led care (p < 0.05) were independent risk factors for perineal trauma. The overall referral rate was low (7%) and was most commonly caused by pathologic cardiotocography (CTG) and prolonged first- and second-stage of labor. Most referred mothers nevertheless had spontaneous deliveries (77%), and there were low rates of vaginal operative deliveries and cesarean sections (vacuum extraction, 16%; cesarean section, 7%). Conclusions The present study confirmed that midwife-led care confers important benefits and causes no adverse outcomes for mother and child. The favorable obstetrical outcome clearly highlights the importance of the selection of obstetric care, on the basis of previous risk assessment. We therefore fully support the recommendation that midwife-led care be offered to all low-risk women and that mothers should be encouraged to use this option. However, to increase the numbers of midwife-led care deliveries in Austria in the future, it will be necessary to expand this care model and to establish new midwife-led care units within hospital facilities.